Peningkatan Produksi Tanaman Padi Sawah (Oryza Sativa L.) dengan Beberapa Jenis Mulsa dan Beberapa Varitas Pada Metode System of Rice Intensification (SRI) - Amir Mahmud; Muhklis Hasibuan (Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2018)
The study was conducted in the village of Purwodadi, Padangsidimpuan City. The purpose of this study was to examine the increase in production of lowland rice (Oryza sativa L.) in the System Of Rice Intensification method. This experiment uses a Split plot design in a RAK pattern with two factors. The main factor is lowland rice variety consisting of three treatment levels, namely Aryze H6444 variety, Situ Bagendit variety, and Siganteng variety. The subplot factor is the use of mulch which consists of four treatment levels namely rice straw, rice husk, tithonia, and black plastic mulch. Siganteng variety with plastic mulch application showed the highest and lowest panicle lengths were found in the interaction between Aryze H6444 Gold variety and rice husk mulch application. Siganteng variety with mulch application of rice straw showed the highest average number of unprocessed rice. The highest planted fresh grain weight in Siganteng Variety interaction with rice straw mulch was not significantly different from the interaction of Siganteng variety with rice husk mulch. The highest 1000 grain weight was found in the interaction between Siganteng varieties and rice husk mulch. The highest dry weight of grain per plant was found in the interaction of Siganteng varieties with plastic mulch. The highest production potential is found in the interaction of Siganteng varieties with plastic mulch which shows an average of 16.85 tons/ha. The lowest average is found in the interaction of Aryze H6444 Gold variety with tithonia mulch which shows an average of 7.15 tons/ha. Keywords: mulch, variety, system of rice intensification